PENGEMBANGAN BAHAN AJAR IPA TERPADU MELALUI LESSON STUDY PADA MATERI BAHAN KIMIA TAMBAHAN UNTUK MAKANAN - Izati, Azmi; Mantini, Sri; N. Subekti, N. Subekti (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2013)
Hasil pengamatan menunjukkan bahwa pembelajaran IPA terpadu belum diterapkan di beberapa Sekolah Menengah Pertama (SMP), salah satunya adalah SMPN 3 Muntilan. Hal ini dikarenakan kekurang pemahaman guru tentang IPA terpadu dan selama ini buku yang digunakan tidak menarik untuk dibaca dan dipelajari, sehingga hasil belajar siswa tidak mencapai Kriteria Ketuntasan Minimal (KKM). Berdasarkan alasan tersebut maka dikembangkanlah bahan ajar IPA terpadu melalui lesson study pada materi bahan kimia buatan untuk makanan. Penerapan pembelajaran Lesson study bertujuan mengembangkan profesi guru untuk mengatasi kegagalan siswa dalam belajar. Metode penelitian yang digunakan adalah Research and Development untuk menghasilkan bahan ajar IPA terpadu dan menguji keefektifannya. Hasil penelitian menunjukkan bahwa bahan ajar IPA terpadu sangat layak untuk digunakan dalam proses pembelajaran. Penggunaan bahan ajar IPA terpadu berpengaruh terhadap nilai siswa sehingga 86% nilai siswa mencapai Kriteria Ketuntasan Minimal. Ketuntasan nilai siswa juga dipengaruhi oleh peningkatan profesi guru dalam pembelajaran lesson study. The observation showed that integrated science learning has not been applied in several Junior High Schools, one of them is SMPN 3 Muntilan. The reason was most of teachers did not understand what is meant by integrated science, and further the books they are using are not enjoyable in terms of readibility and learnability. Therefore, the learning result was not reaching the minimum mastery criteria. For those reasons an integrated science teaching material was developed by implementing the lesson study in the learning material of artificial chemical for food. The aim of implementations of lesson study was to develop a teachers’ profession to overcome the students’ failure. The research design was Research and Development to produce integrated science teaching material and verify its effectiveness. The research showed that teaching material was very appropriate so that it could be use on the learning process. The use of teaching material had an effect on students’ grade, in that 86% the grade of students was reaching the minimum mastery criteria. The increasing students’ grade is also affected by the teachers’ profession. The conclusion of this research was that integrated science teaching material was very appropriate criteria so that it could be used on the learning process and can help students to get better grade over 75.